Efficacy of EUS-guided keyhole biopsies in diagnosing subepithelial lesions of the upper gastrointestinal tract - Verhoeve, Sen; Verloop, Cynthia; Bruno, Marco; Terpstra, Valeska; Van Driel, Lydi; Perk, Lars; Hol, Lieke (Endoscopy International Open, 2024)
Background and study aims Tissue acquisition is required for diagnosis of subepithelial lesions (SELs). However, obtaining adequate tissue remains challenging. This study investigated an EUS-guided technique using a forceps to create a channel and take multiple biopsies from the center of the lesion, therefore called endoscopic ultrasound-guided keyhole biopsy (EUS-KB).Patients and methods A retrospective cohort study was conducted in 56 patients with SELs in the upper gastrointestinal tract who were scheduled to undergo EUS-KB. The primary aim was to assess diagnostic yield, defined as the percentage of procedures where EUS-KB resulted in a definitive histopathological diagnosis. Furthermore, factors influencing diagnostic yield were investigated. Additional outcomes included technical success and adverse events.Results Technical success was achieved in 55 of 60 biopsies (91.7%). EUS-KB provided a diagnosis in 44 of 55 biopsies (80.0%), histology mostly showing gastrointestinal stromal tumor or leiomyoma. The diagnostic yield was not significantly influenced by the size or location of the SEL. Adverse events occurred in one patient (1.7%).Conclusions EUS-KB is a feasible and safe technique for obtaining a classifying diagnosis for SELs in the upper gastrointestinal tract. It could offer an alternative diagnostic modality, especially in lesions smaller than 20 mm.
Keywords: Endoscopic ultrasonography; Subepithelial lesions; Tissue diagnosis; Quality and logistical aspects; Performance and complications